Biomechanical report for the IAAF World Indoor Championships 2018 60m hurdles women - Walker, J.; Pollitt, L.; Paradisis, G.; Bezodis, I.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2019)
The women`s 60 m hurdles took place on the evening of Saturday 3rd March. In the lead up to the event, Sharika Nelvis (United States) was the likely favourite following her time of 7.70 s in Albuquerque (USA) only two weeks previously, a time that was enough to place her third on the all-time indoor list with the fastest time for over ten years. Kendra Harrison and Christina Manning (both United States) were also likely favourites given their incredibly fast times throughout the season. The race was ultimately dominated by Kendra Harrison, who joined Sharika Nelvis as the third fastest all-time with a time of 7.70 s, breaking the Championship Record along the way. Nelvis herself could only manage fourth place, as Christina Manning and Nadine Visser (The Netherlands) claimed the silver and bronze medals, respectively.